Altered Spontaneous Brain Activity and Functional Integration in Hemodialysis Patients With End-Stage Renal Disease - Su, Huanhuan; Fu, Shishun; Liu, Mengchen; Yin, Yi; Hua, Kelei; Meng, Shandong; Jiang, Guihua; Quan, Xianyue (Frontiers in Neurology, 2022)
Purpose: Using the amplitude of low-frequency fluctuation (ALFF) and functional connectivity (FC) algorithm to study the alteration of brain function in hemodialysis patients with end-stage renal disease (ESRD). Patients and methods: We recruited 20 ESRD patients on regular hemodialysis and 17 healthy controls. All of the participants underwent resting-state fMRI (rs-fMRI), neuropsychological tests, and blood biochemical examination. The individual ALFF values between the two groups were tested by Independent sample t-test. Then we set the altered ALFF brain areas as seed regions of interest (ROIs), and FC analysis was used to investigate the functional integration patterns between the seed ROI and the voxels within the whole brain. Results: The ALFF values of right precuneus and angular gyrus (RAG) in the ESRD group were lower than those in healthy control subjects, but the right precentral gyrus showed higher ALFF values in patients. Hemoglobin (Hb) was negatively correlated with the ALFF values of the right precentral gyrus, and the ALFF values of right precuneus was negatively correlated with line tracing test (LTT) scores in ESRD patients. ESRD patients show decreased connectivity between the RAG and the left precuneus, right superior frontal gyrus (RSFG), and the connectivity within the RAG was weak. In addition, functional connectivity in the RAG-right cuneus, right precuneus-left supramarginal gyrus was enhanced in the patient group. Conclusion: Our research suggested that, in the hemodialysis patients with ESRD, the brain areas with abnormal spontaneous brain activity and functional connectivity are mainly located in the default mode network (DMN) regions. Hb and the LTT results were correlated with abnormal spontaneous brain activity. These findings provide additional evidence to understand the possible underlying neuropathological mechanisms in ESRD patients.